ปัจจัยที่ทำให้คนมารักษาโรคด้วยพลังจักรวาล - ปริญญาพร สินหนู (จุฬาลงกรณ์มหาวิทยาลัย, 1998)
The Purpose of this research was to find the reasons why people cure diseases with the Universal Energy. Here, 7 factors were considered : basic or fundamental need, family & kinship , friends ,mass communication, serious disease , psychological need and appreciation in organization This research is also compare the Role of Curing Disease with the Universal Energy between Foundation of Universal Energy and Wat Khaema Pirataram and Wat Paknum, Nonthaburi. The research Technics were General Observation, Participant Observation, Key Informant Interview, In-Depth Interview and Informal and Formal Interview. Besides the purpose of the research is to understand the ways of curing diseases with the Universal Energy.The Hypothesis are as the following. 1. Basic need caused people to cure diseases with the Universal Energy. 2. Family and Kinship had influence on curing diseases with the Universal Energy. 3. Friends had influence on curing diseases with the Universal Energy. 4. Mass communication had influence on curing diseases with the Universal Energy. 5. Serious Diseases had influence on curing diseases with the Universal Energy. 6. Psychological need had influence on curing diseases with the Universal Energy. 7. Appreciation in Organization had influence on curing diseases with the Universal Energy The finding was in accordance with all of the hypothesis except Number 4.